2018
DOI: 10.3390/ijms19010183
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Performances of Protein Function Prediction Algorithms from the Perspectives of Identification Accuracy and False Discovery Rate

Abstract: Abstract:The function of a protein is of great interest in the cutting-edge research of biological mechanisms, disease development and drug/target discovery. Besides experimental explorations, a variety of computational methods have been designed to predict protein function. Among these in silico methods, the prediction of BLAST is based on protein sequence similarity, while that of machine learning is also based on the sequence, but without the consideration of their similarity. This unique characteristic of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 122 publications
(152 reference statements)
0
14
0
Order By: Relevance
“…Conversion of sequences into vector revealed good results in both groups used for analysis ( Table 1, 2 and Supplementary Table S2). In protein study, protein sequence converted into feature vectors showed good performance in cases of SVM and KNN (57)(58)(59)(60). RF00174, RF00059, RF00504, RF00522 predicted better than others with minority classes like RF01054, RF00634, RF00380 ( Table 1 and 2).…”
Section: Discussionmentioning
confidence: 99%
“…Conversion of sequences into vector revealed good results in both groups used for analysis ( Table 1, 2 and Supplementary Table S2). In protein study, protein sequence converted into feature vectors showed good performance in cases of SVM and KNN (57)(58)(59)(60). RF00174, RF00059, RF00504, RF00522 predicted better than others with minority classes like RF01054, RF00634, RF00380 ( Table 1 and 2).…”
Section: Discussionmentioning
confidence: 99%
“…This particular event was also observed in the relaxed condition of gene cluster detection for functional classification (Ling, et al, 2009). It has been also shown that ML efficiently assigns protein function (Yu, et al, 2018) and predicts the gene cluster that holds functional coupling (Chuang, et al, 2012). In this study, we applied the ML approach with gene neighborhood-based feature to facilitate the photosynthetic function assignment.…”
Section: Discussionmentioning
confidence: 99%
“…Diverse methods for proteomic data processing (transformation, normalization, and imputation) profoundly affected the precision of protein quantification which was frequently assessed using the value of pooled intragroup median absolute deviation (PMAD) of reported protein intensity among replicates ( Chawade et al, 2014 ; Kuharev et al, 2015 ; Valikangas et al, 2018 ; Yu et al, 2018 ). Particularly, the PMAD was designed to demonstrate the capacity of each analysis chain to reduce the variation among replicates, and therefore to enhance the technical reproducibility ( Chawade et al, 2014 ).…”
Section: Methodsmentioning
confidence: 99%